Crystallochemical aspects of structure controlled processes in oxide glasses - Stoch, Leszek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Nano size crystals formation in SiO2–Al2O3–MgO–TiO2(ZrO2) glasses as a structure controlled process is described. The applicability of the structure – chemical parameters for prediction and modelling of the middle range ordering in glass as a nanocrystals precursor are presented.
Optica Applicata, Vol. 38, 2008, nr 1, s. 225-235
Keywords: optyka; oxide glasses; middle range structure ordering; nano-crystallization; glass-ceramics